Real-time communication in 802.11 networks: The virtual token passing VTP-CSMA approach - Ricardo Moraes (2006)
Currently there is a trend for the implementation of industrial communication systems on top of wireless communications. However, keeping up with the timing constraints of real-time traffic in open medium environments is a hard task. The main source for complexity is that, if the set of communicating devices is not previously agreed, the timing constraints imposed by such devices cannot be predicted at the system setup time, nor can be effectively controlled at the system run-time. In this paper, we propose the VTP-CSMA architecture to deal with this problem. This architecture allows the coexistence of default IEEE 802.11e devices with real-time devices sharing the same communication medium, enabling the prioritization of real-time traffic. The proposed solution is based on the control of the medium access rights by means of a Virtual Token Passing procedure (VTP), complemented by an underlying traffic separation mechanism that prioritizes realtime traffic over the traffic from default IEEE 802.11 stations. The simulation analysis shows that the VTP-CSMA architecture guarantees values for both the throughput and the average access delay that significantly improves the results obtained for default IEEE 802.11e stations operating under EDCA mode.